2015
DOI: 10.1155/2015/962637
|View full text |Cite
|
Sign up to set email alerts
|

miR-1322 Binding Sites in Paralogous and Orthologous Genes

Abstract: We searched for 2,563 microRNA (miRNA) binding sites in 17,494 mRNA sequences of human genes. miR-1322 has more than 2,000 binding sites in 1,058 genes with ΔG/ΔG m ratio of 85% and more. miR-1322 has 1,889 binding sites in CDSs, 215 binding sites in 5′ UTRs, and 160 binding sites in 3′ UTRs. From two to 28 binding sites have arranged localization with the start position through three nucleotides of each following binding site. The nucleotide sequences of these sites in CDSs encode oligopeptides with the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…For this reason, the miR-5-15733-3p and miR-17-39416-3p binding sites in the region encoded polyAla, and in the mRNA region from 11193 nt to 11264 nt -polyGly. The assumption that a single nucleotide sequence of binding polysites can encode the oligopeptide in the three reading frames has been confirmed in the study of miR-1322-3p binding with the mRNA of 48 human genes that demonstrated the way of polyGln, polySer and polyAla were encoded by miR-1322-3p (Niyazova et al, 2015;Atam bayeva et al, 2017). Synonymic codons of the miRNA binding sites in the mRNAs of Hsa, Csa and Pab were used in the ratios GGC 18 GGU 2 AGU 1 , GGC 15 GGU 5 AGU 1 and GGC 16 GGU 2 AGU 1 , respectively.…”
Section: Molecular and Cell Biology Vavilov Journal Of Genetics And Bmentioning
confidence: 93%
“…For this reason, the miR-5-15733-3p and miR-17-39416-3p binding sites in the region encoded polyAla, and in the mRNA region from 11193 nt to 11264 nt -polyGly. The assumption that a single nucleotide sequence of binding polysites can encode the oligopeptide in the three reading frames has been confirmed in the study of miR-1322-3p binding with the mRNA of 48 human genes that demonstrated the way of polyGln, polySer and polyAla were encoded by miR-1322-3p (Niyazova et al, 2015;Atam bayeva et al, 2017). Synonymic codons of the miRNA binding sites in the mRNAs of Hsa, Csa and Pab were used in the ratios GGC 18 GGU 2 AGU 1 , GGC 15 GGU 5 AGU 1 and GGC 16 GGU 2 AGU 1 , respectively.…”
Section: Molecular and Cell Biology Vavilov Journal Of Genetics And Bmentioning
confidence: 93%
“…Binding sites encode a polyglutamine oligopeptide ranging from six to 47 amino acids in length. Data indicated the importance of conserve� n�cleoti�e seq�ences of miR-1322 binding sites and not only the amino acid seq�ence correspon�ing to oligopepti�es of the enco�e� protein [24]. miR-1281 bin�s in mRNA of CACNA1I, PVRL1 and EGR1, genes.…”
Section: Resultsmentioning
confidence: 97%
“…The miR-1322 binding sites has arranged binding sites were arranged in the CDSs of the orthologous genes MAMLD1, MAML2, and MAML3 genes. These sites encode a polyglutamine oligopeptide ranging from six 6 to 47 amino acids in length [1,10].…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…Numerous microRNAs (miRNAs) that regulate the expression of several hundred genes by binding to their mRNAs have been identified [1][2][3][4]. These miRNAs play key roles in the regulation of many biological processes and changes in their concentrations are observed in various pathologies in humans and other animals [5][6][7].…”
Section: Introductionmentioning
confidence: 99%